PENGEMBANGAN BAHAN AJAR E-BOOK MENGGUNAKAN FLIPBOOK PADA SUBTEMA DAERAH TEMPAT TINGGALKU - Annisa Salsabila; Nurlinda Safitri; Yudhie Suchyadi (STKIP Subang, 2023)
This research aims to determine the development of E-books using flipbooks in class IV subtheme 2 in the area where I live in class IV at SDN Dewi Sartika, Bogor Regency and to determine the feasibility of flipbook-based E-books in the learning process. The method used in this research is the Research and Development (R&D) method with the ADDIE model. In this research, validation tests have been carried out on several experts in the media, language and material fields to develop and perfect e-book products using flipbooks for students. . The data results from media expert validation were 96%, which means that e-books are very suitable for testing. The linguist obtained a result of 94.54%, which means it was declared very suitable for testing. And based on trials that have been carried out on classIV students, 24 students obtained a score suitable for use in the learning process of 91.11% and trials that have been carried out on teachers amounted to 90%, which means that the E-book product using this flipbook is very suitable for use in the learning